Integration of HACCP principles in developing centralised kitchen concept towards safer foods in Junior Science Colleges in Perak and Kedah, Malaysia - Abd Lataf, Dora Liyana (2022)
Students aged 7 to 17 years were exposed to the risk of food poisoning, which aref associated with unhygienic preparation of foods sold and served in schools. The problem with the current conventional foodservice system is it poses high microbiological risk of food safety issues, has no food safety assurance program, very short food shelf-life, and time-consuming. The cook-chill method is the most efficient system for a central kitchen where foods are cooked, packaged, and rapidly chilled before transported to satellite kitchens. MARA Junior Science Colleges (MJSCs) in Perak and Kedah were selected because these states has the most number of MJSCs in Malaysia and the proposed centralised kitchen is located in Perak. The objectives of this study are (i)to evaluate the food safety and hygiene knowledge, attitude, and practices (KAP) of food handlers and managers in MJSCs; (ii)to develop a hazard analysis critical control point (HACCP) system for cook-chill centralised kitchen; (iii)to validate the cooking process using isothermal inactivation method; (iv)to validate the rapid chilling process by evaluating microbial growth before and after chilling process; and (v) to validate the cold storage by real-time shelf-life study on cook-chill beef kurma. Food safety KAP surveys were administered to MJSCs kitchen food handlers using a self-administered questionnaire, on-site observation, and personal interview. Development of a HACCP system and improvement on current Standard Operating Procedures for the cook-chill central kitchen in preparation of the cook-chill beef cooked in spices dish were based on MS1480:2019. Validation for cooking of beef was determined using the isothermal inactivation method whereby whole muscle beef inoculated with Salmonella Enteritidis and Salmonella Typhimurium was cooked in four different temperatures at different time intervals. Bacteria's survival rate was plotted. Multi-point mapping was used to identify hot spot in blast chiller in the validation of rapid chilling process. The cold storage shelflife validation of cook-chilled beef kurma was carried out for 4-days using a real-time shelf life study and microbiological, physicochemical, and sensory quality were determined. This study shows that all food handlers (n=134) have excellent knowledge, a positive attitude, and good self-reported practices regarding food safety and hygiene with a mean percentage(SD) score of 65.2%(12.7), 92.3%(16.2), and 73.0%(15.0) respectively. However, on-site observation conducted shows some practices are different from the ones reported by the food handlers. Three processes were determined as CCPs, which are the cooking of beef, rapid chilling, and cold storage. The D-values for the cooking of whole muscle beef are D58 o C=5.41min, D60 o C=2.03min, D62 o C=0.46min and D64 o C=0.18min. The validation of rapid chilling found that there is no significant difference in microbial growth befor and after chilling process of beef kurma at 0-3oC for <120 minutes. In the cold storage shelf-life validation, the microbiological quality food tested was within the acceptable limit for all 4-days. By using the duo-trio test, panellists could differentiate between the freshly cooked beef kurma and cook-chill beef kurma (p<0.05). Findings from this study present an insight into food safety towards the implementation of the HACCP principles and food preparation in developing a cookchill centralised kitchen concept in schools’ foodservice operations.